Analysis of social capital and its involvement in the development of various economic structures - Kamichi, Manuel (2021)
The main objective of this article is to analyse what is the share capital and the different economic structures that can be developed from the presence of this type of capital; to this end, conceptual research on the term and its main characteristics has first been used; Afterwards, various models of economic structures have been gathered that were built through social capital. To this end, the methodology that has been used is the review of 126 secondary sources. Through research it is discovered that social capital is used to develop various forms of economic structures in different spaces and times such as cooperatives, self-managed models, civil organizations and networks of interinstitutional relations in multiple contexts where everyone has in common the presence of this type of capital. The models described are characterized by the presence of strong social ties based on values such as solidarity, cooperation, mutual assistance and trust.